PEMANFAATAN FERMENTASI REBUNG UNTUK BAHAN SUPLEMEN PANGAN DAN TEPUNG SERAT - Rachmadi, Andri Taruna (Kementerian Perindustrian, 2011)
One of the solutions to fulfillÂ the food sustainability is diversification of local food. One of the local food that potential to be used and processed is bamboo shoots. In South Kalimantan, the potential of bamboo as a producer of bamboo shoot plants with an estimated total area of 2158 hectares with a potential of 6 million stems. To increase the value and health of bamboo shoots can be made with fermentation. Fermentation is done by two methods, enzimatic fermentation and spontaneous fermentation. The results of the highest crude fiber obtained in spontaneous fermentation of bamboo shoots Haur 44.46% while the highest starch content present in fermented bamboo shoots Paring stater of 13.91%. Metal content, everything is still fulfill the quality standard. Flour bamboo shoots can be used as food supplements or raw materials of fiber flour.Keywords: bamboo shoots, Â fermentation, fiber flour